Islamic authority figures and (their) religioscapes in Muslim Indonesia - Seise, Claudia (Azizah) (2018)
In this paper, I will especially focus on how we can obtain a better understanding of the influence a particular religious authority figure has on the people within his/ her reach. Religious authority figures in Indonesia, I argue, form the core from which a particular religioscape can develop. A religioscape is a dynamic social space where one religious practice and/ or religious interpretation is predominant. At the same time, religious authority figures are influenced by the historically grown religioscape in which they live. This mutual process affects the people living in a particular religioscape. With the example of three religious authority figures and their respective learning institutions, I aim to illustrate how Muslim personalities influence and form the religioscape that surrounds them. The first case study is grounded in the mystic Islam found in Yogyakarta. The second case study explores the mixture of local and Hadhrami influences in the Islamic practice of South Sumatra, while the third case study examines an ‘imported’ form of reform Islam in a transmigrasi settlement. Of major importance in these case studies will be what actually influences the religious authority figure and what tools he uses to disseminate his thoughts and interpretations of Islam. I argue that, the concept of the religioscape enables us to understand deeper the impact religious authority figures have on their surroundings and vice versa, and that it can serve as a methodological tool to grasp the diverse plurality of Islamic practices in Indonesia.